## 1 + cot^2x =

### To simplify the expression 1 + cot^2x, we can use the identity for cotangent:

cot^2x = csc^2x – 1

Substituting this identity into the expression, we have:

1 + cot^2x = 1 + (csc^2x – 1)

Now, we combine like terms:

1 + cot^2x = 1 + csc^2x – 1

The 1 and -1 cancel out, leaving us with:

1 + cot^2x = csc^2x

Therefore, the simplified expression is csc^2x

To simplify the expression 1 + cot^2x, we can use the identity for cotangent:

cot^2x = csc^2x – 1

Substituting this identity into the expression, we have:

1 + cot^2x = 1 + (csc^2x – 1)

Now, we combine like terms:

1 + cot^2x = 1 + csc^2x – 1

The 1 and -1 cancel out, leaving us with:

1 + cot^2x = csc^2x

Therefore, the simplified expression is csc^2x.

##### More Answers:

Understanding Point-Slope Form | An In-Depth Explanation of this Essential Math ConceptThe Pythagorean Identity | Unraveling the Fundamental Relationship between Sine and Cosine

Simplifying a Trigonometric Expression | The Identity Involving Tangent and Secant Functions

Error 403 The request cannot be completed because you have exceeded your quota. : quotaExceeded